(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
This article examines the efficacy of the communicative approach in the acquisition of language skills. The communicative approach, emphasizing interaction and practical usage of language, has gained prominence in modern language teaching methodologies. This study aims to evaluate its effectiveness compared to traditional methods by reviewing recent research, analyzing classroom implementations, and assessing language proficiency outcomes. Key areas of focus include speaking, listening, reading, and writing skills. The findings suggest that the communicative approach significantly enhances learners’ communicative competence and fluency, particularly in speaking and listening. Furthermore, the study explores the role of cultural context and the integration of authentic materials in language instruction. The article concludes with recommendations for educators on best practices for implementing the communicative approach to maximize language acquisition outcomes.